Characteristics of Clinical and Electrophysiological Pattern in a Large Cohort of Chinese Patients With Charcot-Marie-Tooth 4C - Duan, Xiaohui; Ma, Yan; Fan, Dongsheng; Liu, Xiaoxuan (Frontiers in Neurology, 2021)
The “Src homology 3 (SH3) domain and tetratricopeptide repeats 2” (SH3TC2) gene is mutated in individuals with Charcot-Marie-Tooth disease (CMT) and considered relevant to a demyelinating or intermediate subtype of CMT disease, CMT4C. In this study, we screened a cohort of 465 unrelated Chinese CMT patients alongside 650 controls. We used Sanger, next-generation, or whole-exome sequencing to analyze SH3TC2 and other CMT-related genes and identified 12 SH3TC2 variants (8 novel) in 7 families. Of the 8 novel variants, 7 were likely pathogenic (c.280–2 A > G, c.732–1 G > A, c.1177+6 T > C, c.3328–1 G > A, G299S, R548W, L1048P), and 1 had uncertain significance (S221P). The CMT4C frequency was calculated to be 4.24% in demyelinating or intermediate CMT patients without PMP22 duplication. Additionally, we detected variant R954* in the Chinese cohort in our study, indicating that this variant may be present among Asians, albeit with a relatively low frequency. The onset age varied among the 8 patients, 3 of whom presented scoliosis. We diverse phenotypes in the Chinese CMT cohort and concluded that the absence of scoliosis, cranial nerve involvement, or late-onset symptoms does not necessarily preclude SH3TC2 involvement in a given case.